Surface-termination dependence of propanoic acid deoxygenation on Mo2C - Kim, Seok Ki; Kim, Jaehoon; Lee, Seung-Cheol (ELSEVIER SCIENCE BV, 2017)
Although Mo2C is used as an alternative catalyst material for biomass conversion, the dependence of its reaction on the type of surface termination has not been studied. In the present study, we performed density functional theory calculations for the deoxygenation of propanoic acid on the two types of surface terminations possible for orthorhombic Mo2C (100), namely, on Mo-and C-terminated surfaces. The reaction energetics of the three possible deoxygenation pathways, namely, those for hydrodeoxygenation, decarbonylation, and decarboxylation, were compared by calculating the activation energies for their key surface reactions, such as hydrogenation and the scission of C-C, C-O, and O-H bonds. The Mo-terminated surface was advantageous in the case of the hydrodeoxygenation pathway because of its low kinetic energy barrier for the hydrogenation of the oxygen species, while the C-terminated surface preferred the decarboxylation pathway because of its low kinetic energy barrier for O-H bond scission.
Keywords: TRANSITION-METAL CARBIDES; DENSITY-FUNCTIONAL THEORY; ELASTIC BAND METHOD; MOLYBDENUM CARBIDE; CATALYTIC DEOXYGENATION; PROCESSING BIOMASS; REACTION PATHWAYS; VEGETABLE-OILS; CO ADSORPTION; HYDRODEOXYGENATION